Exocets no Facebook: subjetividades bombardeadas e captura do desejo na rede social - Santiago, Anderson Cacilhas (2019)
The research investigates the production of subjectivities in the field of Facebook page comments managed by newspapers, social movements, political parties and personalities, where the narratives are disputed by actors, hybrid personas that are articulated in the network. Uses the actor-network-theory, by Bruno Latour (2012), as a methodological guideline, hybridized it with quantitative data and graphs. The actors, in a symmetrical relationship with the researchers, tell how they act in a politically polarized network. The hybrid personas are organized in networks where multiple is substantive, which makes the research also advance to the organization of network wars and other possible configurations on Facebook. With Donna Haraway (2009), a reflection on the relationship of people with algorithms and bots and about blurred boundaries between human and machine is promoted, which results in the hybrid personas. The analysis advances considering the network as part of the architecture that humans make of themselves, such as upgrading their body, adding that to a broad reflection on fake news and post-truth. The conversations with the actors were made from the use of a hybrid persona created for research: Kátia Flávia. She made interventions in the field considering natural analyzers, emerged from street demonstrations, the arrest of former president Lula, or the 2018 elections, among others, events always related to political polarization. A dialogue with Suely Rolnik (2016) raises the idea of subjectivities constantly shaken on Facebook as a result of deterritorialization that causes malaise in the network actors, which in turn is converted into hatred and resentment channeled against "scapegoats." This has fueled movements that flirt with fascism and raises leaders fabricated on this treadmill. Desire has its captured creative force and its potency used so that the subjectivities, purchased ready on the shelves of the current system, are recomposed, maintaining the status quo. An active micropolitical action is proposed as part of the resistance to capture the creative force by a system that alliances with political forces that embody rude characters with archaic and pre-republican ideas. To compete with this movement, it would be necessary to displace the narratives of the macropolitical construction traditionally partisan, syndical and social movements. In networks, identities are fractured and groups tend to form from affinities